IoT-Based Low-Voltage Power Distribution System Management and Control Platform - Tong, Li; Zhou, Jinhui; Li, Junyi (Frontiers in Energy Research, 2022)
In order to improve the operational safety and market operation efficiency of the prosumer energy community, to achieve comprehensive monitoring of abnormalities, fault alarms and intelligent control and maintenance, and to reduce the risk of information security, and to address the many types of operational testing and metering equipment in the prosumer community, but the duplication of functions and hardware composition, resulting in the waste of resources of monitoring and metering equipment. In the meantime, we propose an intelligent perception device-based IOT platform architecture for power distribution communities by integrating the software and hardware of the original operation monitoring and metering equipment of the prosumer integrated communities. The intelligent perception device for community IOT sensing is firstly introduced, and then the operation monitoring and metering equipment in the distribution station area is integrated and optimized to enhance the panoramic state sensing capability of the intelligent terminal; and the expansion application direction of data-driven distribution IOT is proposed from the typical application scenario of the terminal.